MACHIAVELI IN SAAVEDRA FAJARDO, THE SHADOW OF VIRTUE - Hermosa Andújar, Antonio (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
Unintentionally, Saavedra develops his political doctrine, even from the election of the political subject itself, as opposed to the guidelines stated by Machiavelli. The immanent presence of ethics and religion as active parts of the above mentioned doctrine indicates so. However, in describing the behaviour the Spanish monarch should pursue in a political sphere, Saavedra discovers and ends up owning that spheres considered complementary at first, have become antagonistic. And by accepting how politics sometimes survive only by infringing the dictates of ethics, he ends up becoming as well another member of Machiavelli’s large critical wake turned loyal disciples at the end.
Keywords: Saavedra; Machiavello; Spanish monarchy; ethics; religion; political stability